Home, school and the museum: shifting gender performances and engagement with science. Issue 2 (17th February 2020) - Godec, Spela
Abstract: Research has highlighted that engagement with science is highly gendered and that the masculinised culture of science makes it difficult for many girls/women to engage. Meanwhile, a growing body of research has explored the potential of out-of-school spaces to provide more equitable engagement opportunities. In this paper, I examine engagement with science among working-class, self-identified 'girly' girls aged 11-13. I discuss how gender performances and engagement with science shifted across science lessons, school trips and family trips to science museums. The findings suggest that engagement with science is complex, contradictory and varies across spaces – girls' performances of hyper-femininity supported engagement with science in some spaces, but made it difficult in others. Different spaces also afforded the girls different opportunities for performing gender, which in some instances opened up new ways for engaging with science. I conclude by discussing the implications for more equitable science education.